2019
DOI: 10.1039/c8an02192a
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of boronic acid-decorated carbon nanodots as optical nanoprobes for glycoprotein sensing

Abstract: Synthesis-modification-doping-integration: one-step synthesis of boronic acid-decorated carbon nanodots for glycoprotein sensing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Some studies have justied that quenching occurs due to particle aggregations. 42,45,46 Boron hybridization changes and/or the presence of nonradiative channels induced by electrostatic forces-aggregation/disaggregation caused by the anionic form of the boronic acid upon analyte complexation is another possible mechanism for the quenching. 47 The lack of knowledge on the mechanism of saccharide complexations and how it affects luminescence indicates an open eld for further investigations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have justied that quenching occurs due to particle aggregations. 42,45,46 Boron hybridization changes and/or the presence of nonradiative channels induced by electrostatic forces-aggregation/disaggregation caused by the anionic form of the boronic acid upon analyte complexation is another possible mechanism for the quenching. 47 The lack of knowledge on the mechanism of saccharide complexations and how it affects luminescence indicates an open eld for further investigations.…”
Section: Resultsmentioning
confidence: 99%
“… 44 Phenylboronic acid and ethylenediamine were used to produce functionalized C-dots for detecting glycoproteins. 45 It is important to note that the examples mentioned above are selective, reproductive and presented good detection limits. However, in all cases, the probes responses are associated with luminescence quenching.…”
Section: Resultsmentioning
confidence: 99%
“…The three BCDs (including blue-emitting BCDs (B-BCDs), green-emitting BCDs (G-BCDs), and red-emitting BCDs (R-BCDs)) were prepared based on previous work, and details of the synthesis are given in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…The aggregation of QDs resulted in fluorescence quenching. Zhang et al suggested that glycoprotein HRP could induce the aggregation and fluorescence quenching of boronic acid-decorated carbon nanodots (CNDs) [ 168 ]. However, the “turn-off” detection system may interfere with other substances in the complicated matrix, leading to a “false positive” result.…”
Section: Boronate-affinity-based Fluorescent Assays and Imagingmentioning
confidence: 99%